2022
DOI: 10.3390/en15062283
|View full text |Cite
|
Sign up to set email alerts
|

Review on Material and Design of Anode for Microbial Fuel Cell

Abstract: Microbial Fuel Cell (MFC) is a bio-electrochemical system that generates electricity by anaerobic oxidation of substrates. An anode is the most critical component because the primary conversion of wastewater into electrons and protons takes place on the surface of the anode, where a biofilm is formed. This paper describes the essential properties of the anode and classifies its types according to the material used to make it. Anode material is responsible for the flow of electrons generated by the microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Likewise, the microbial taxonomic classes, which are significantly dominant, were Gammaproteobacteria and bacilli. Interestingly, as discussed above, the MFC produced a higher electrical current with PANI than rGO and CNTs as doping material to the composite www.nature.com/scientificreports/ powder on the anode, even though the latter two graphene-based materials possess better conductivity and are conventionally used to harvest electrical power in MFC 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the microbial taxonomic classes, which are significantly dominant, were Gammaproteobacteria and bacilli. Interestingly, as discussed above, the MFC produced a higher electrical current with PANI than rGO and CNTs as doping material to the composite www.nature.com/scientificreports/ powder on the anode, even though the latter two graphene-based materials possess better conductivity and are conventionally used to harvest electrical power in MFC 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multiwalled carbon nanotubes showed higher performance than single‐walled carbon nanotubes when used as anode in the presence of a hydroxyl group. The open circuit potential was 0.75 V, and the output power was 167 mW m −2 , which is 130 % more than that of carbon fabric 83.…”
Section: Electrode and Membrane Materials For Mesmentioning
confidence: 90%
“…In addition, most metal electrodes are highly corrosive and not biocompatible. The maximum power density achieved with a noncorrosive metal, such as stainless-steel anodes, was about 70 mW m -2 [83].…”
Section: Electrode Materials For Mesmentioning
confidence: 99%
“…Throughout time, numerous sorts of materials have been utilized to manufacture anodes. Different carbonaceous materials are widely applied as the material for the anode in an MFC [ 21 ]. Additionally, some metals and metal oxides have also been used as the material for anodes.…”
Section: Architectural Design For Mfc Constructionmentioning
confidence: 99%
“…However, some of the metals do not facilitate biofilm formation. Studies have shown that non-corrosive metals such as stainless steel could not produce increased power density due to poor bacterial adherence [ 21 ]. Other than this, different noble metals, such as platinum, titanium, gold, etc., have also shown improved performances.…”
Section: Architectural Design For Mfc Constructionmentioning
confidence: 99%